2012
DOI: 10.1155/2012/416073
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Weaning from Nasal CPAP in Preterm Neonates

Abstract: Objective. Identification of the weight and postmenstrual age (PMA) at successful weaning of NCPAP in preterm neonates and the factors influencing the successful wean. Study Design. Retrospective review of 454 neonates ≤32 weeks of gestational age (GA) who were placed on NCPAP and successfully weaned to room air was performed. Results. Neonates had a mean birth weight (BW) of 1357 ± 392 grams with a mean GA of 29.3 ± 2.2 weeks. Neonates were weaned off NCPAP at mean weight of 1611 ± 432 grams and mean PMA of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 35 publications
4
36
1
Order By: Relevance
“…There were fewer PBs in the fast group with a PDA compared to those in the slow group, and a co-linearity association between PDA and both GA and Bwt was observed. However, no association between CPAP ceasing and PDA was identified, which was in agreement with the results obtained from previous authors [14,23]. Others have found a PDA especially if prolonged and significant is associated with longer ventilation and CLD [18,26].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There were fewer PBs in the fast group with a PDA compared to those in the slow group, and a co-linearity association between PDA and both GA and Bwt was observed. However, no association between CPAP ceasing and PDA was identified, which was in agreement with the results obtained from previous authors [14,23]. Others have found a PDA especially if prolonged and significant is associated with longer ventilation and CLD [18,26].…”
Section: Discussionsupporting
confidence: 91%
“…Linear regression results showed that Bwt was the only significant negative predictor for both CPAP duration and CPAP ceasing attempts. Our study found that for every 100-g increase in Bwt, there is a decrease in CPAP duration by 0.4 weeks, compared to the decrease in 0.2 weeks found by a recent trial [23]. The reason for the difference may be the GA and Bwt of the PBs in our study ranged from 25-29 weeks and 0.5-1.5 kg, respectively, compared with those of 24-32 weeks in GA and 0.6-2.6 kg in Bwt of others [23,27].…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In this study, no association was found between GA and the appearance of lesions in preterm infants receiving nasal septum NIV. Such association is directly related to the appearance of skin lesions due to the immaturity of the tissues (10,(27)(28)(29)(30) .…”
Section: Resultsmentioning
confidence: 99%